THE USE OF INTERNET-ASSISTED LANGUAGE TEACHING FOR EFL CLASSROOM IN INDONESIAN MADRASAH - Fauziah, Zumrotul (Borneo Journal of English Language Education, 2020)
The rapid development of technology affects all aspects of life includes education. It becomes essential for teachers to possess skill or competencies on using the internet technology for teaching. Teachers’ belief and competencies affects their attitude towards the use of internet technology for teaching. The aim of this study is to explore the teachers’ perceptions of the use of Internet-Assisted Language Teaching (IALT) for EFL Classroom in Indonesian Madrasah (Islamic School). The data of this survey study is collected through questionnaire and interview. The questionnaires are distributed on-line using Google form to 35English teachers of Madrasah in several regions of Indonesia, but only 26 returned. The data was analyzed using descriptive statistics and interpreted comprehensively. The result of the study shows that the majority of the English teachers in Madrasah have positive learning experience and positive attitude toward the use of IALT in their EFL classroom. However, they perceived that they lack of competencies and less knowledge to use the internet for teaching. Therefore, they need internet technology training to improve their skill in using and integrating internet technology for teaching EFL classroom.